Logika Fuzzy Mamdani Untuk Mendukung Keputusan Pembelian Laptop Asus M409BA Berdasarkan Spesifikasi Yang Tersedia - Muhammad Redy Hermawan; Reshi Alam (STMIK Budi Darma, 2020)
Fuzzy logic can be applied to solve various problems that exist today, one of which is by using the fuzzy mamdani method. In today's technological developments, many people need laptops for their daily activities. Many types of laptops are available on the market today, which makes it difficult for many consumers to determine the best choice. From these problems the authors decided to create a decision-making system in order to help provide laptop recommendations to customers according to the criteria that consumers want. The variables used to determine the laptop according to consumer desires are based on the screen size, the price of the laptop, and the capacity of the available random access memory (RAM). Because these criteria are not absolute, calculations are made using the fuzzy mamdani method in order to get the right choice of what the customer does not know. Based on data on laptops on the market, the authors test using the Mamdani fuzzy method to get decisions that make it easier for consumers.